Influence of substrate type on transport properties of superconducting FeSe0.5Te0.5 thin films. (17th April 2015) - Yuan, Feifei; Iida, Kazumasa; Langer, Marco; Hänisch, Jens; Ichinose, Ataru; Tsukada, Ichiro; Sala, Alberto; Putti, Marina; Hühne, Ruben; Schultz, Ludwig; Shi, Zhixiang
Abstract: FeSe0.5 Te0.5 thin films were grown by pulsed laser deposition on CaF2, LaAlO3 and MgO substrates and structurally and electro-magnetically characterized in order to study the influence of the substrate on their transport properties. The in-plane lattice mismatch between FeSe0.5 Te0.5 bulk and the substrate shows no influence on the lattice parameters of the films, whereas the type of substrate affects the crystalline quality of the films and, therefore, the superconducting properties. The film on MgO showed an extra peak in the angular dependence of critical current density J c ( θ ) at θ = 180° ( H || c ), which arises from c -axis defects as confirmed by transmission electron microscopy. In contrast, no J c ( θ ) peaks for H || c were observed in films on CaF2 and LaAlO3 . J c ( θ ) can be scaled successfully for both films without c -axis correlated defects by the anisotropic Ginzburg–Landau approach with appropriate anisotropy ratio γ J . The scaling parameter γ J is decreasing with decreasing temperature, which is different from what we observed in FeSe0.5 Te0.5 films on Fe-buffered MgO substrates.